KOMPARATIF TREND HARGA PANGAN BERAS SAAT PANDEMI COVID 19 DI PULAU SUMATERA (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
This study aims to see a comparison of rice food price trends during the COVID-19 pandemic on the island of Sumatra. This research was deliberately conducted on the island of Sumatra, which consists of 10 provinces as research samples. The research method uses historical methods that occur today. Using secondary time series data (times series) from monthly report data from March 2020 to February 2021. The data analysis method uses the trend equation with the least squares method. The results of the research study, namely the island of Sumatra with 10 provinces, only the Riau Islands where there was an increase in rice prices of Rp. 150. In three provinces, the price of rice fell by more than 50 percent, namely Riau, Bengkulu and Lampung. Meanwhile, Aceh, North Sumatra, West Sumatra, Jambi, South Sumatra and Bangka Islands experienced price declines. And the trend of rice food prices for the next five years will continue to increase. Keywords: Comparative, Trend, Food, Rice